Interaction of serotonin and cholecystokinin in the lateral parabrachial nucleus to control sodium intake - De Gobbi, JIF; De Luca, L. A.; Johnson, A. K.; Menani, José Vanderlei [UNESP] (Amer Physiological Soc, 2001)
Serotonin [5-hydroxytryptamine (5-HT)] and CCK injected into the lateral parabrachial nucleus (LPBN) inhibit NaCl and water intake. In this study, we investigated interactions between 5-HT and CCK into the LPBN to control water and NaCl intake. Male Holtzman rats with cannulas implanted bilaterally in the LPBN were treated with furosemide + captopril to induce water and NaCl intake. Bilateral LPBN injections of high doses of the 5-HT antagonist methysergide (4 mug) or the CCK antagonist proglumide (50 mug), alone or combined, produced similar increases in water and 1.8% NaCl intake. Low doses of methysergide (0.5 mug) + proglumide (20 mug) produced greater increases in NaCl intake than when they were injected alone. The 5-HT2a/2c agonist 2,5-dimetoxy-4-iodoamphetamine hydrobromide (DOI; 5 mug) into the LPBN reduced water and NaCl intake. After proglumide (50 mug) + DOI treatment, the intake was not different from vehicle treatment. CCK-8 (1 mug) alone produced no effect. CCK-8 combined with methysergide (4 mug) reduced the effect of methysergide on NaCl intake. The data suggest that functional interactions between 5-HT and CCK in the LPBN may be important for exerting inhibitory control of NaCl intake.
Keywords: 5-hydroxytryptamine; proglumide; methysergide; NaCl intake; sodium appetite; angiotensin II